Analysis of the Factors of Educated Unemployment in Faryab Province - Morwat, Ahmad Farid; Arsalan, Zahra (Integrated Journal for Research in Arts and Humanities, 2024)
The country's educational system has experienced rapid growth in the past two decades. Increased educational capacity through the establishment of universities and higher education institutions has led to a significant increase in university graduates without aligning with the needs of the job market. This research aims to analyze the factors of educated unemployment in Faryab province. A sample size of 384 was determined using a random sampling method, and data was collected through questionnaires. Furthermore, Spearman's correlation coefficient was used to determine the relationship between variables. The research results showed a significant relationship between educational, socio-cultural, economic, and managerial factors. According to the findings: a) A negative relationship was found between educational factors and educated unemployment in Faryab province, with a correlation coefficient of -0.716. b) A strong negative relationship exists between socio-cultural factors and educated unemployment in Faryab province, with a correlation coefficient of -.836. c) A negative relationship was found between economic factors and educated unemployment in Faryab province, with a correlation coefficient of -.793. d) A strong negative relationship also exists between managerial factors and educated unemployment in Faryab province, with a correlation coefficient of -0.896.